Mineral dust observed with AERONET Sun photometer, Raman lidar, and in situ instruments during SAMUM 2006: Shape-independent particle properties - Müller, Detlef; Weinzierl, Bernadett; Petzold, Andreas; Kandler, Konrad; Ansmann, Albert; Müller, T.; Tesche, Matthias; Freudenthaler, Volker; Esselborn, Michael; Heese, Birgit; Althausen, Dietrich; Schladitz, A.; et al. (Journal of Geophysical Research, 2010)
Aerosol Robotic Network (AERONET) Sun photometer observations were carried out at Ouarzazate, Morocco, during the Saharan Mineral Dust Experiment (SAMUM) 2006. Data from one measurement day, 19 May 2006, are used to derive particle optical and microphysical parameters with AERONET's latest version of lightÃ¢ÂÂscattering model for nonÃ¢ÂÂspherical particle geometry. In our analysis we also make use of a novel measurement channel at 1638 nm wavelength. We compare the results to data products obtained by airborne highÃ¢ÂÂspectralÃ¢ÂÂresolution lidar, several groundÃ¢ÂÂbased Raman lidar, and airborne and groundÃ¢ÂÂbased in situ measurement platforms. We chose that specific measurement day because the dust plume was vertically well mixed. Extinction coefficients from AERONET Sun photometer and lidar observations and in situ measurements agree well. ÃÂngstrÃÂ¶m exponents from Sun photometer and lidar are in close agreement, too. Airborne in situ measurements of dust particle size distributions show larger effective radii than inferred from the AERONET data. Complex refractive indices that are derived with the AERONET algorithm differ from the values obtained with different independent techniques employed in our study. The singleÃ¢ÂÂscattering albedo was derived from the airborne observations of particle size distributions and complex refractive indices. SingleÃ¢ÂÂscattering albedo differs to the value inferred from the AERONET data. The differences may be attributed to the different effective radii that we obtained from the various techniques. The differences between the data products from the various measurement platforms, however, cannot be generalized, as we could only test data for one measurement day. An analysis of additional measurements is under way.